Efecto del color y de la densidad de la funda de polietileno en la presentación y calidad del racimo de banano - Barba Herrera, Lenin Stalin (2012)
This context of the interest of farmers, arose the need that the banana farms in the province and the country certify the use of bags of polyethylene to secure the quality of the fruit, and detaches the importance of conducting this test of research with the following objectives: 1. determine the impact of the color and density of the sheath of polyethylene in the increase in diameter and weight in the last three hands; 2. Establish treatment with higher performance in the bunch of bananas; 3 Determine cost of production. The present research work carried out in the hacienda ¨Reina of the Cisne¨, with a dry climate without excess heat or warm water, mega. Cut rainy period and much of the year presents water deficit, its average annual temperature is 25 ° C. Number nine, treatments consisted in an arrangement factorial of four colors of the polyethylene green, pink, grey, white and blue for the conventional witness and the insecticides Chlorpyrifos, Malathion and a witness with blue sleeve without insecticide. The following variables were evaluated: weeks to the filling of the fingers. The Coleoptera Colaspis damage submetallica jacobi in the first and second hand. Damage caused by thrips of the flower Franklinella parvola Hood and red spot Chatanaphotrips signipennis in the second and final hand. Index of damage produced by the presence of cochineal Dismicoccus brevipes. Texture of the bark of the fingers. Resistance to the spoiling of the fingers, colour of the crust of the fingers, and decline. The color of the cover is a factor that allows somehow interfere with the colonization of thrips of the red spot, especially the pink colors and gray, condic to obtain the highest percentage of healthy bunches. The Thrips of the red spot is currently the scourge of major economic significance in the banana region by high populations which reaches in the field. Color covers provided satisfactory protection for damage caused by thrips of the flower which taxonomically corresponds to Frankliniella parvola Hood. The insecticides chlorpyrifos and Bifenthrin incorporated into polyethylene covers provided a similar control of adults of Colaspis submetallica jacobi. With the texture of the crust colour covers they reached high values and the intense green color was superior to the treatment in which employment cover blanca.